HOW THEATER WITHIN A TRANSFORMATIVE ORGANIZING FRAMEWORK CULTIVATES INDIVIDUAL AND COLLECTIVE EMPOWERMENT AMONG LGBTQQ YOUTH. Issue 7 (September 2014) - Wernick, Laura J.; Kulick, Alex; Woodford, Michael R.
<x xml:space="preserve">Abstract</x> Lesbian, gay, bisexual, transgender, queer, and questioning (LGBTQQ) youth experience oppression in their schools and communities, which creates barriers to their healthy development. Emerging research documents strategies to support LGBTQQ youth, but little is known about developing LGBTQQ youth empowerment. This study extracts qualitative data (key informant interviews, n = 8, and a focus group, n = 8) from a larger case study of an LGBTQQ youth organization that uses theater within a transformative organizing model to make their schools safer and more inclusive. Findings suggest that theater–both theater games used within the group and scripted performances for adult stakeholders–uniquely contributed to developing individual and collective empowerment through an iterative process of building community, cultivating critical consciousness, and providing opportunities to effect change. Encouraging creative expression alongside developing LGBTQQ youth's capacity to create change can contribute to the positive development of LGBTQQ youth.